DETERMINAN KEBAHAGIAAN PEREMPUAN BEKERJA DI INDONESIA: ANALISIS DATA INDONESIA FAMILY LIFE SURVEY - Nisrina Nursyiana; Badriyah, Nurul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this research is to analyze the determinants of happiness for working women in Indonesia. Using the cross-sectional data of Indonesia Family Life Survey (IFLS) wave 5, a number of 3,368 observations were selected using logistic model. This model was chosen because the dependent variables are categorical, and the normal assumption is in error distribution. This study finds that wage is still relevant to be used as a measure for welfare in Indonesia due to the absence of Easterlin Paradox in Indonesia. Higher wages enable the public to have more freedom in fulfilling their consumptive needs. Furthermore, non-economic factors such as education, age, and marital status influence the happiness of working women, while residence is not influential. Furthermore, “double burden” borne by married working women does not reduce their happiness because marriage helps them in financial security from difficult economic conditions, in addition to economic factors and specialization in their family that can increase income.